KAJIAN PERAN MOTIVASI KOMUNIKASI LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA PERUMDA PERGUDANGAN DAN ANEKA USAHA “PEDARINGAN” KOTA SURAKARTA - Hartati Dyah Wahyuningsih; Yudo Kisworo (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2020)
Abstract-The purpose of this study is to find out, empirically test and analyze motivation, communication, and work environment on organizational commitment and the performance of employees of Perumda Warehousing and Various Businesses